Phylogenetic relationships and evolutionary history of the Early Paleogene genus Igorina through parsimony analysis - D.M. Soldan; M.R. Petrizzo; I. Premoli Silva; A. Cau (2011)
The evolution of planktonic foraminifera in the Paleocene-Eocene time interval is characterized by a high rate of diversification after the major extinction event observed at the Cretaceous/Paleogene boundary. The accelerated speciation rate resulted in the appearance of several new genera (i.e., Igorina and Acarinina among others) each of them identified on the basis of distinctive wall texture of the shell. Phylogenetic relationships within many genera are still poor understood including the origin and phylogeny of the genus Igorina. This group, characterized by a thick, nonspinose and incrusted wall, appears in Subzone P3a (early late Paleocene) and disappears in Zone E9 (middle Eocene). To date, nine species have been assigned to the genus Igorina (I. pusilla, I. trichotrocha, I. tadjikistanensis, I. convexa, I. albeari, I. laevigata, I. lodoensis, I. broedermanni and I. anapetes) based on both wall texture and morphologic similarities. This study is aimed to reconstruct the phylogeny and evolution of the igorinid species with cladistic analysis by applying the method of parsimony. To perform the study, two hundred samples have been analysed from Ocean Drilling Program (ODP) Leg 198 Hole 1209B (Shatsky Rise, Central Pacific Ocean), Leg 143 Hole 865B (Allison Guyot, Central Pacific Ocean), Leg 15 Sites 151 and 152 (Caribbean Sea) and Leg 113 Hole 690B. The biostratigraphic analysis of sub-tropical localities revealed some problems in applying the previous biostratigraphic scheme (Berggren and Pearson, 2005) mainly because some marker species 1) have been misinterpreted and/or misidentified several times in previous studies, 2) show a delayed appearance with respect to what reported from other localities, and 3) are very rare or absent in the studied samples. Species identification was mainly performed through comparison with the original descriptions and illustrations and partially follows Subbotina (1953), Blow (1979), Olsson and others (1999), Pearson and others (2006). Phylogenetic relationships of the ...